KRITERIA DAN INDIKATOR UNTUK PENILAIAN TINGKAT KESIAGAAN DESA DALAM PENGENDALIAN KEBAKARAN HUTAN DAN LAHAN - Kushartati Budiningsih; Irfan Malik Setiabudi; Elvida Yosefi Suryandari; Deden Djaenudin; Mohamad Iqbal (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2020)
The government have prioritized forest and land fires issue become one of their national priorities. Villagebased fire control Approach have been Developed by Encouraging community involvement. That approach considers an existence of village as the site-smallest administrative entity and also fire events occur within village. The validated criteria and indicators are utilized as an instrument for assessing the preparedness performance of villages, specifically on fires control. Those instruments comprise 5 criteria and 20 indicators, which represent their different weight for each. The criteria encompass community participation, technology and infrastructure, land and livelihood, fire control team, and fire control policy. Those instruments have been developed in 5 provinces, comprise South Sumatra, Jambi, West Kalimantan, Central Kalimantan, and South Kalimantan. Thus, it can generate classification of fire-preparedness village as following Class A (Good), B (Moderate), and C (Poor). Tarung Manuah (Central Kalimantan) and Jangga Baru (Jambi) villages are an example of village which have a good preparedness condition on fire control (Class A). This assessment tool is easy to use and can be practiced by all parties, in the form of self-assessment. Further, this instrument and its classification can be optimized as a basis for village-based program interventions on conducting fire control.